The Sociology Of Environmental Activism Among High School Students: A Study Of Islamic Religious Education, Ecoteology, And The Green School Movement - Muh. Hanif; Naela Wirdianul Ulya (Penerbit Presisi Pustaka, 2026)
The global climate crisis demands the contribution of educational institutions in shaping an environmentally conscious character. This research aims to analyze students' environmental activism at MAN Purbalingga through the integration of ecotheology-based Islamic Religious Education (PAI) and the Adiwiyata School program. Using a descriptive qualitative method, data were collected through observation, semi-structured interviews with the madrasah community, and documentation, which were then analyzed using the Miles and Huberman interactive model. The results show that MAN Purbalingga successfully constructed a solid green ecosystem through the synergy of three main elements: theological strengthening in Akidah Akhlak subject materials (specifically the concept of iffah), social habituation such as the